Of horses and swords: The 25 May and the Wars of Independence in text books of the third cycle of basic general school of "educational transformation" of the 90s - De Amézola, Gonzalo Alvaro (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2010)
This article analyzes the changes in the narrative of the independence of Argentina that the educative reform tried to introduce in textbooks for the third cycle of General Basic Education, the new compulsory education path defined by the reform of the 90s. These changes included an update of transmitting knowledge in school and the skills that history should be promoted in the classroom.